Usage information: Depends on you / Hasfarini Hassim and Darlina Darmansah - Hassim, Hasfarini; Darmansah, Darlina (2015)
If we heard about the word "information", many assortments come in our mind. Society interpretation towards information was information is a knowledge that can be assessed through a variety of formats as for example through mass media, like newspapers and conferences, social media such as twitter, facebook, Instagram and so forth. In brief, information is data that is processed or formulated in the form of codes which is symbol or a sound in which humans need to encode the messages and adapt them in a verbal and non- verbal communication. It is ideas, opinions, notions, word, or something new that can be shared as a new knowledge to all users. However, it is not an extraordinary to us to hear the misuse of information cases. Fraud does not just happen in big organizations only, but without realizing it, we as individually can also lead to misappropriation of information. This is not an easy fact to be accepted as a whole, but this is the reality Sometimes, our actions may lead to plagiarism when we copy others works without credited the author or owner of the information used. In fact, the way of the adaptation, maintenance, and management information lies in us. If we have an identity, have a faith, principles and ethics, we will respect the rights of others as we care for our own rights. We are the creator which characterize ourselves what we want to do. Therefore, we cannot just blaming and pointing on others because we must always remember that when we blame on others, the other three fingers was turned again to ourselves.